Important curing agents used for rapid curing: a systematic review - Neves, Roberta Motta; Agnol, Lucas Dall; Monticeli, Francisco Maciel [UNESP]; Ornaghi, Heitor Luiz (Elsevier, 2023)
Thermosetting composites are an important class of materials for several applications. However, depending on the resin and agent curing type, the curing stage could take a long time (several hours) for a complete chemical crosslink of the resin, obtaining excellent mechanical properties, which is far beyond the targeted manufacturing cycle. The development of rapid curing agents is one strategy to minimize this drawback by considerably decreasing the curing time of the thermosetting polymers. From this perspective, this book chapter is devoted to a systematic review of curing agents applied for rapid curing on thermosetting polymers, focusing on the main findings of the last 10 years. The search was done based on preferred reporting items for systematic reviews and meta-analyses protocol and elaborated as a systematic review focusing on predefined primary search, avoiding bias in selecting studies. After the primary search, 29 studies were included in the review and presented, focusing on the curing agent type, processing, resin, and characterizations. This chapter allows the readers an easy identification of the main trends and gaps in the field as well as future perspectives.
Keywords: Curing agent; resin; systematic review; thermosetting polymers